Effect of substituted phenylamine antioxidants on three life stages of the freshwater mussel Lampsilis siliquoidea. (October 2017) - Prosser, R.S.; Gillis, P.L.; Holman, E.A.M.; Schissler, D.; Ikert, H.; Toito, J.; Gilroy, E.; Campbell, S.; Bartlett, A.J.; Milani, D.; Parrott, J.L.; Balakrishnan, V.K.
Abstract: Substituted phenylamines (SPAs) are incorporated into a variety of consumer products (e.g., polymers, lubricants) in order to increase the lifespan of the products by acting as a primary antioxidant. Based on their physicochemical properties, if SPAs were to enter the aquatic environment, they would likely partition into sediment. No studies to date have investigated the effect of sediment-associated SPAs on aquatic organisms. The current study examined the effect of four SPAs (diphenylamine (DPA); N-phenyl-1-napthylamine (PNA); N-(1, 3-dimethylbutyl)-N'-phenyl-1, 4-phenylenediamine (DPPDA); 4, 4'-methylene-bis[N-sec-butylaniline] (MBA)) on three different life stages of the freshwater mussel, Lampsilis siliquoidea . The viability of larvae (glochidia) of L. siliquoidea and Lampsilis fasciola was assessed after 48 h of exposure to SPAs in water. The 48-h EC50s for glochidia viability of L. siliquoidea were 5951, 606, 439, and 258 μg/L for DPA, PNA, DPPDA, and MBA, respectively, and 7946, 591, 137, and 47 μg/L, respectively, for L. fasciola . Juvenile (7–15 months) and adult L. siliquoidea were exposed to sediment-associated SPAs for 28 d. LC50s for juvenile mussels were 18, 55, 62, and 109 μg/g dry weight (dw) of sediment for DPA, PNA, DPPDA, and MBA, respectively. Adult mussels were exposed to sub-lethal concentrations of sediment-associated SPAs in order to investigate reactive oxygen species (ROS), lipid peroxidation and total glutathione in the gill, gonad, and digestive gland tissue, and viability and DNA damage in hemocytes. No significant concentration-dependent trend in any of these biochemical and cellular endpoints relative to the concentration of sediment-associated SPAs was observed in any tissues. Investigations into the concentration of SPAs in the aquatic environment are required before a conclusion can be made on whether these compounds pose a hazard to the different life stages of freshwater mussels. Graphical abstract: Highlights: Substituted phenylamine antioxidants are additives in lubricants and polymers. Viability of larval mussels was reduced by exposure to 47–7946 μg SPA/L water. 50% of juvenile mussels died at concentrations of 18–109 μg SPA/g dw sediment. Oxidative stress and DNA damage not observed in tissues of mussels exposed to SPAs. Abstract : Variation in toxicity of SPAs to different life stages of freshwater mussels (i.e., MBA > PNA/DPPDA > DPA) corresponds with variation in physicochemical properties of SPAs.